The Role of Religious Education in Forming Social Ethics - Imro Atus Soliha; Khozin; Moh. Nurhakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Islamic religious education has a very important role in shaping individual moral and ethical character. By involving the understanding and practice of Islamic teachings, religious education is able to build moral awareness, strengthen faith, and provide direction for positive behavior. Various values such as justice, honesty, politeness, patience and generosity are instilled to form a good personality. Apart from that, Islamic religious education also teaches universal values such as respect for others and environmental conservation. However, Islamic religious education is faced with a number of challenges, including changes in social values and norms, technological advances, and generational transformation. To overcome this, strategies are needed such as developing a relevant curriculum, improving the quality of teachers, utilizing technology and media, collaborating with parents and the community, openness to contextual challenges, and a continuous monitoring and evaluation system. Thus, Islamic religious education can become a solid foundation in forming strong morals and ethics in Muslim individuals.